Genetic variability in the A microsatellite at SLC11A1 gene and possible implications with innate resistance against brucellosis in Algerian native goats - Hossem SAHRAOUI; TOUFIK MADANI; KHALED FANTAZI; ASMA CHAOUCH KHOUANE; ABDELKADER AMEUR AMEUR; PIETRO PASCHINO; GIUSEPPE MASSIMO VACCA; SEMIR BECHIR SUHEIL GAOUAR; MARIA LUISA DETTORI (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Sahraoui H, Madani T, Fantazi K, Chaouch Khouane A, Ameur Ameur A, Paschino P, Vacca GM, Gaouar SBS, Dettori ML. 2020. Genetic variability in the A microsatellite at SLC11A1 gene and possible implications with innate resistance against brucellosis in Algerian native goats. Biodiversitas 21: 5630-5636. Goat rearing is among the major agricultural activities practiced in Algeria. However, brucellosis represents an important threat to the goat sector and to public health. The aim of our work was to characterize the genetic variability of the A microsatellite at the 3' untranslated region (3' UTR) of SLC11A1 gene in Algerian native goat breeds as it was associated with Brucellosis genetic resistance in goat. Genomic DNA samples of 90 goats belonging to the four Algerian native breeds; Mekatia (n = 32), Arbia (n = 30), Dwarf of Kabylia (n = 14) and Mozabit (n = 14) have been analyzed. Polymorphism of region A microsatellite was determined by capillary electrophoresis identifying 8 alleles and 20 genotypes. Genetic parameters were also estimated. Polymorphic information content was PIC = 0.60, the observed and the expected heterozygosity were Ho = 0.569 and He = 0.595, respectively, and the values of FIS, FIT and FST were 0.044, 0.064, and 0.021, respectively. The A microsatellite was highly polymorphic and alleles associated genetic resistance against brucellosis in other breeds or species have been identified. These results open a promising opportunity to implement a genetic improvement program to reduce goat brucellosis spread in Algeria.